RESULTS OF CIRCULATING IMMUNE COMPLEXES OF PATIENTS WITH DISEASES OF THE NOSE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Contradictions remain in the approach to the treatment of diseases of the nose and BYoB. Scientific studies on the evaluation of the effectiveness of various tools in diseases of the nose and BYoBs developed against the background of myocarditis are not many and conflicting. In this case, the use of metabolic agents in various pathologies of the myocardium, according to some authors, is undoubtedly necessary, but others believe that their recommendation is not justified. Thus, at present, there are no universally accepted criteria for diagnosing myocardial damage in diseases of the nose and BYoBs around the world, an algorithm for treating such patients has not been developed, and recommendations for this or that treatment have not been substantiated.